(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role of modern educational technologies in improving the quality and effectiveness of education. In particular, it examines the opportunities provided by digital platforms, interactive methods, and distance learning in individualizing the learning process, developing students’ independent thinking, and improving assessment systems. The impact of innovative approaches on the pedagogical process and their practical significance are also substantiated.